Experimental and numerical evaluation of thermodynamic effect on NACA0015 hydrofoil cavitation in hot water - Le, Anh Dinh (Vietnam Journal of Mechanics, 2021)
In this study, the cavitation in hot water, which implies tight interaction of thermodynamic effect, phase change phenomena, and flow behavior, was studied by a combination of experiment and numerical simulation. The experiment in water up to 90°C was performed in the high temperature and high-pressure water tunnel with NACA0015 as a cavitator. The temperature inside the cavity was measured using the high-accuracy thermistor probe. According to the result, the temperature depression in the cavity was increased proportionally with the increase of freestream temperature. The inverse thermodynamic effect was observed with the increase of cavity length when temperature increased. The maximum temperature depression of about 0.41°C was measured in the water at around 90°C. The temperature drop was reasonably captured in simulation by coupling our simplified thermodynamic model with our cavitation model and governing equations. The tendency of temperature depression in the cavity agreed well with experimental data under different flow conditions.